DNAH17 is associated with asthenozoospermia and multiple morphological abnormalities of sperm flagella. (16th December 2019) - Sha, Yanwei; Wei, Xiaoli; Ding, Lu; Mei, Libin; Huang, Xianjing; Lin, Shaobin; Su, Zhiying; Kong, Lingyuan; Zhang, Yi; Ji, Zhiyong
Abstract: Background: Multiple morphological abnormalities of the sperm flagella (MMAF) is one kind of severe asthenozoospermia, which is caused by dysplastic development of sperm flagella. In our study, we sought to investigate the novel gene mutations leading to severe asthenozoospermia and MMAF. Methods and Materials: The patient's spermatozoa were tested by Papanicolaou staining and transmission electron microscopy. Whole exome sequencing was performed on the patient with severe asthenozoospermia and MMAF. Sanger sequencing verified the mutations in the family. The expression of DNAH17 was detected by immunofluorescence and Western blot. Results: Spermatozoa sample from the patient showed severe asthenozoospermia and MMAF. We detected biallelic mutations (c.C4445T, p.A1482V and c.C6857T, and p.S2286L) in DNAH17 (MIM:610063). The protein expression of DNAH17 was almost undetectable in spermatozoa from the patient with the biallelic mutations. Conclusion: These results demonstrated that DNAH17 may be involved in severe asthenozoospermia and MMAF.